Whose perspective is it anyway? Dilemmas of patient involvement in the development of a randomized clinical trial – a qualitative study. (4th May 2019) - Høeg, Beverley Lim; Tjørnhøj-Thomsen, Tine; Skaarup, Julie Alling; Langstrup, Henriette; Zoffmann, Vibeke; Saltbaek, Lena; Karlsen, Randi Valbjørn; Dalton, Susanne Oksbjerg; Johansen, Christoffer; Bidstrup, Pernille Envold
Abstract: Background: Patient and public involvement (PPI) is increasingly becoming a requirement in the effort to improve the relevance and quality of healthcare research. We examined how involving patients with lower education levels affected PPI in the development of the MyHealth randomized clinical trial of breast cancer follow-up from the perspectives of the patients and professionals. Material and methods: Eight women who had completed breast cancer treatment, four with fewer than 10 years of education, were recruited as members of a patient panel advising researchers in the development of the trial. We carried out individual and focus group interviews with panel members and recruiting nurses between April and September 2016. Researcher observations and changes made based on panel feedback were also documented. Patients were asked to evaluate the process according to a PPI theoretical framework with four dimensions: (i) ways of involvement, (ii) research vs. patient concerns, (iii) strength of the patient's voice, and (iv) degree of change. A combination of inductive and deductive thematic analysis was conducted whereby emerging themes were organized using the above framework. Results: All patient contributors reported high satisfaction with being involved and PPI improved trial materials and recruitment strategy. However, contradictory perspectives between lay and expert approaches to research led to dilemmas not related to educational background. Patients were often more concerned with unmet needs after cancer than with research, and the scientific hierarchy made it difficult for researchers to include the patient perspective if it challenged research requirements. Nurses also faced ethical dilemmas when recruiting patients as PPI contributors. Conclusions: Our findings challenged the assumption that PPI automatically leads to a broad range of patient perspectives that can directly improve research relevance and quality. This highlights the need for more research and better guidance on the use of PPI in research.